NU's 2021 national congress : contestation within - Arifianto, Alexander R. (2022)
Nahdlatul Ulama, Indonesia’s largest Islamic organisation, will hold its national congress tentatively in December 2021. Several leaders representing different theological viewpoints within the organisation have announced their candidacies to be NU's next chairman.